Cross-sectional study of recurrent disc herniation risk factors and predictors of outcomes after primary lumbar discectomy: A STROBE compliance - Yao Christian Hugues Dokponou; Fresnel Lutece Ontsi Obame; Mohamed Mouhssani; El Akroud Sofia; Zineb Siba; Moussa Elmi Saad; Imad-Eddine Sahri; Zakaria Chandide Tlemcani; Napoleao Imbunhe; Diakite Yero; Housni Abderrahmane; Jawad Laaguili; et al. (Interdisciplinary Neurosurgery, 2023)
Objectives: The purpose of this study is to determine if lifting weight, smoking status, occupational work, and diabetes were predictors for recurrent lumbar disk herniation (rLDH) leading to reoperation and if the outcome can be influenced by the reoperated level and side. Methods: From June 2010 to July 2019, the 2196 consecutive patients who underwent first-time single-level lumbar discectomy at our institution were revised. Data on first lumbar spine surgery, reoperation as well as preoperative data were brought into the analysis. Multivariate Logistic Regression Analysis was performed to determine whether lifting weight, smoking status, occupational work, and diabetes were predictors for recurrent lumbar disk herniation. The outcome level was assessed by the Multivariable Cox-regression Kaplan–Meier analysis for repeated lumbar disc herniation excision at the L4L5 and L5S1 levels independently. Results: From the 101(4.59%) patients that presented with recurrent lumbar disc herniation (rLDH), 75 cases (3.41%) met the inclusion criteria. There were 54 cases of ipsilateral recurrent herniation and 21 contralateral with a male predominance of 64% (n = 48). The average age at the time of recurrence was 48 ± 9.34 years (age range 29–67 years). The group of diabetes patients who smoke is at high risk (Odds 2.77) of rapid recurrence for lumbar disc prolapse; about 3 months after the first surgery followed by the group of diabetes who lift weight (Odds 0.83), about 4 months after the first surgery. At the L4L5 level, only the group of patients operated for opposite side recurrence (Odd ratio 1.01) did well and were pain-free immediately after surgery compared to the group of patients operated for recurrence on the same side (Odd ratio 6.73). Conclusion: Coexisting diabetes and smoking status in the same patient increase the risk of rLDH and the patient’s outcome is favorable with pain-free after reoperation without the need for physiotherapy when the recurrence is on the same level and opposite side.